PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA KEPALA SEKOLAH TERHADAP PRODUKTIVITAS KEPALA SEKOLAH MENENGAH ATAS NEGERI DI PROVINSI DKI JAKARTA - DEDE HAMDANI; SITI NURJANAH (Fakultas Ekonomi Universitas Negeri Jakarta, 2014)
Abstract This study aims to determine the influence of organizational culture and job satisfaction with work productivity state secondary school principals in the province of Jakarta. This study used survey method with path analysis technique (Path Analysis). The data collection process is done by using a questionnaire as a research instrument in this study Head of State High School In Jakarta selected as the unit of analysis with a sample size of 115 people is determined by simple random techniques (simple random sampling). The results show: First, There is influence between organizational culture with job satisfaction; Second, There is the influence of the culture of the organization with the principal productivity. Thirdly, There is the influence of job satisfaction on work productivity. Keywords: organizational culture, job satisfaction, productivity